Antibacterial activities of methanol extract of Ziziphus mauritiana leaves on cariogenic bacteria / Hasnah Begum Said Gulam Khan ... [et al.] - Said Gulam Khan, Hasnah Begum; Samsuddin, Zuhairah; Mohd Sarmin, Nurul ‘Izzah; Ramlee@Rambely, Azlin Sham (2019)
Dental caries, is one of the most chronic diseases which have affected almost half of the world’s population making it the major global oral health problem in the world. It is also known as biofilm-mediated multifactorial disease that occurs when the cariogenic bacteria disrupted the homeostatic balance of plaque biofilm, thus initiate disease process. Plant extracts have been used for thousands of years in the prevention and treatment of various diseases. Demand for naturally derived product that are safe, effective and economical has been increased due to adverse effect of some commercially available antibacterial agent currently used in dentistry. Thus, in the current study, methanol extracts of Ziziphus mauritiana (ZM) leaves have been used to study its effect on the most common cariogenic bacteria (Streptococcus mutans and Streptococcus sobrinus). The antibacterial activities were conducted using disk diffusion test (Kirby-Bauer Test). The methanol extract of ZM showed higher activity on S. mutans with the zone of inhibition of 15.67±0.58mm compared to S. sobrinus (0.00mm). The extract that showed antibacterial activity was tested to determine the Minimal Inhibitory Concentration (MIC) and Minimal Bactericidal Concentration (MBC). The MIC and MBC was observed for S. mutans were 100 mg/ml and 200 mg/ml respectively. Treated and untreated sample were submitted for scanning electron microscopy study. The cell treated with ZM extract showed the loss of extracellular matrix formation and disruption of the cell morphology. The phytochemicals study reveals the presence of alkaloids, phenols, tannins, flavonoids and saponin in methanol extract of ZM. Thus, this study showed the potential effect of methanol extracts from Ziziphus mauritiana leaves as a natural agent that can be incorporated in oral health care products.